2013 28th Annual ACM/IEEE Symposium on Logic in Computer Science 2013
DOI: 10.1109/lics.2013.23
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Matching and Linear Programming in Fixed-Point Logic with Counting

Abstract: We establish the expressibility in fixed-point logic with counting (FPC) of a number of natural polynomial-time problems. In particular, we show that the size of a maximum matching in a graph is definable in FPC.This settles an open problem first posed by Blass, Gurevich and Shelah [BGS99], who asked whether the existence of perfect matchings in general graphs could be determined in the more powerful formalism of choiceless polynomial time with counting. Our result is established by showing that the ellipsoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…We now turn to prove Theorem 6, which states that the weak optimization problem for explicitly given SDPs is expressible in FPC. Our result generalizes the previous work by Anderson et al [3], [4] that established the FPC-definability of linear programming, as stated in Theorem 5. In the same fashion as in their work, the central piece of the proof is a formulation of the ellipsoid method in FPC.…”
Section: Expressing Semidefinite Programssupporting
confidence: 89%
See 2 more Smart Citations
“…We now turn to prove Theorem 6, which states that the weak optimization problem for explicitly given SDPs is expressible in FPC. Our result generalizes the previous work by Anderson et al [3], [4] that established the FPC-definability of linear programming, as stated in Theorem 5. In the same fashion as in their work, the central piece of the proof is a formulation of the ellipsoid method in FPC.…”
Section: Expressing Semidefinite Programssupporting
confidence: 89%
“…We show that there is an interpretation in fixed-point logic with counting (FPC) that can, for an explicitly given semidefinite program, define its optimal solution, up to a given approximation. This result generalizes earlier work by Anderson et al [3], [4] who showed an analogous result for the case of linear programs. Extending their techniques, our proof is centered around formalizing the ellipsoid method for solving SDPs in logic.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Note that this proof is similar to the "lemma on a quadrangle" from[Dinitz et al 1976], but that proof does not immediately go through because C ∩ C may not be a (s, t)-cut. 7 Note that the conference version[Anderson et al 2013] of the present paper includes an independent proof of this theorem.Journal of the ACM, Vol. V, No.…”
mentioning
confidence: 99%
“…In the case of 3-colourability, there is also a construction that deploys bijection games (as in [7]) directly to show that this problem is not decidable by such families. These lower bounds should be contrasted with the fact that the existence of perfect matchings in graphs is definable in the logic FPC [2] and therefore is decidable by polynomial-size symmetric threshold circuits.…”
Section: Cai-fürer Immerman Graphsmentioning
confidence: 99%